(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the conditions of globalization, the newspaper-journalistic style undergoes significant changes and adaptations, which causes global processes to affect the topics, structure, and language of journalistic materials. It should be said that in the conditions of globalization, the newspaper journalism method remains an important tool for shaping public opinion and covering events, and journalism is developing significantly in covering new realities. After all, newspaper language reflects social reality, society structure, values, and cultural characteristics. Today, in world linguistics, researches related to the newspaper-journalistic style, as a reflection of the material and spiritual values of the society, require modern new methods and approaches to solve various national-cultural identity issues together with traditional linguistic analysis methods.